Characterisation of pressure and velocity of air flow through perforated pipe: experimental and computational approach / Helmisyah Ahmad Jalaludin, Mohd Daniel Bakri Omar and Ow Chee Seng - Ahmad Jalaludin, Helmisyah; Bakri Omar, Mohd Daniel; Seng, Ow Chee (2017)
Air flow distribution has become one of the most important components that contribute to Heating, Ventilation and Air Conditioning (HVAC) system. Recently, perforated pipe has been chosen to be included into the air flow distribution system due to its effectiveness in distributing air through perforated holes. In this paper, characteristics of air flow through perforated pipe are measured by experiment and computational simulation in order to investigate the pressure distribution as well as velocity distribution along the pipe. Basic equations such as momentum and continuity equations are used to calculate the air flow characteristics. Air flow characteristics through perforated pipe depends on many parameters such as pipe materials, size of hole, pipe diameter and fan speed which could lead to the variation of air flow characteristics. This research has been carried out to investigate the characteristics of the air flow through perforated pipe for the fan speed of 5, 10, 15 and 20 m/s. Also, the dimension for the apparatus has been scaled to a certain ratio that is going to be suitable for experimental investigation. Results show increament in the value of velocity through all four fan speeds. The pressure readings show pressure drop occurs from the inlet to the end of the perforated pipe. Surface roughness of inner pipe and turbulence characteristic at the end of pipe could be the cause of pressure drop and velocity fluctuation.